Prominent Themes of Local Poetry in Pakistan and their Relationship with Urdu - Hassan, Uzma (sourcecoder, 2024)
Apart from Urdu, many languages are spoken in Pakistan, some of them are small and some are big according to the number of speakers, but despite being the languages of Pakistan, they are strangers in their country, their country and confined in limited areas. Have been done. The main reason for this is that there is no organization at the government level to connect these languages with each other and to make a plan together with each other. The national language of Pakistan is Urdu and the official language is English. Correspondence in the offices is in English and common colloquialism is in Urdu. Boards are written in English and spelled in Urdu or local language. From a cultural point of view, Urdu was also not a language of Pakistan but a foreign language. Before the formation of Pakistan, the local languages of the region are spoken here. This article is based on the relation with poetry of Urdu with local languages of Pakistan.